The undisclosed renminbi basket: are the markets telling us something about where the renminbi - US dollar exchange rate is going? - Michael Funke; Marc Gronwald (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
On 21 July 2005 China adopted an undisclosed basket exchange rate regime. We formally assess and envisage the gradual evolution of the renminbi over time. We utilize nonlinear dependencies in the renminbi exchange rate and describe the smooth transition of the renminbi/U.S. dollar (RMB/USD) exchange rate using the family of time-varying autoregressive (TV-AR) models. Specifically, the nonlinear models allow for a smooth transition from one optimal level to another. Our estimation results imply that the RMB/USD ex-change rate will likely be about 7.42 RMB/USD in summer/autumn 2008.
URN:NBN:fi:bof-201408072218
Keywords: C22; F31; F37; 330; China; renminbi; de facto exchange rate regime; TV-AR model; TV-AR-GARCH model